2017
DOI: 10.3892/ol.2017.5858
|View full text |Cite
|
Sign up to set email alerts
|

IL-35 expression is increased in laryngeal squamous cell carcinoma and in the peripheral blood of patients

Abstract: Abstract. has been proposed as a novel immune-suppressing cytokine. However, the function of IL-35 in malignant diseases is yet to be elucidated. The present study investigated IL-35 expression levels in laryngeal squamous cell carcinoma (LSCC) tissues and the peripheral blood of patients to explore the potential involvement of IL-35 in LSCC progression. In the present study, IL-35 expression levels in tissues and peripheral blood were analyzed by reverse transcription-quantitative polymerase chain reaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…IL-35 has led many scholars to study its expression regulation, molecular signalling and immunoregulation. Recent studies have shown that IL-35 is overexpressed in a variety of tumours [ 24 27 ]. It can be used directly in tumour cells to regulate the expression of related proteins, and it also plays an important role in the occurrence and development of tumours by inducing the production of regulatory T cells, inhibiting the response of effector T cells, regulating anti-tumour immune response and inducing immune escape [ 10 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-35 has led many scholars to study its expression regulation, molecular signalling and immunoregulation. Recent studies have shown that IL-35 is overexpressed in a variety of tumours [ 24 27 ]. It can be used directly in tumour cells to regulate the expression of related proteins, and it also plays an important role in the occurrence and development of tumours by inducing the production of regulatory T cells, inhibiting the response of effector T cells, regulating anti-tumour immune response and inducing immune escape [ 10 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In brief, 100 μL of cell suspension (5000 cells) was seeded into each well of a 96-well plate. The plate was incubated for the indicated time periods (12,24,36,48, 60 and 72 h) in an incubator at 37 °C in 5% CO 2 , and 10 μL of CCK-8 solution was added to each well of the plate. The plate was again incubated for 1 h, and the absorbance at 450 nm was measured using a microplate reader.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…It is reported that B cells 21 and tumor‐associated macrophages 22 could also secrete IL‐35 in cancer. High serum level of IL‐35 was always associated with worse prognosis in several cancer types, such as nonsmall cell lung cancer, 23 breast cancer, 24 prostate cancer, 25 laryngeal squamous cell carcinoma, 26 and hepatocellular carcinoma 27 …”
Section: Discussionmentioning
confidence: 99%
“…anti-inflammatory and immunosuppressive factor. 16,17 Although has been reported to be involved in plenty of pathological processes such as inflammatory diseases and autoimmune diseases, 18,19 cancer, 24 prostate cancer, 25 laryngeal squamous cell carcinoma, 26 and hepatocellular carcinoma. 27 The association between IL-35 and GC prognosis has not been clari- 29,30 The main function of FOXP3+ Tregs is secreting cytokines including IL-35, and they are highly expressed in HP-positive patients than in HP-negative patients.…”
Section: Association Between Serum Il-35 and Prognosis Of Gcmentioning
confidence: 99%
“…IL-35 is composed of an Epstein-barr virus-induced gene 3 (EBI3) subunit and IL-12A (p35) subunit (6). Previous studies demonstrated that IL-35 expression was increased in a variety of tumor tissues, including pancreatic ductal adenocarcinoma (PDAC), colorectal cancer, renal cell carcinoma and laryngeal squamous cell cancer (7–10). Furthermore, IL-35 was demonstrated to promote tumor angiogenesis and inhibit the anti-tumor cytotoxic lymphocyte response (11).…”
Section: Introductionmentioning
confidence: 99%